The clinical and paraclinical correlates of employment status in multiple sclerosis - Srpova, Barbora; Sobisek, Lukas; Novotna, Klara; Uher, Tomas; Friedova, Lucie; Vaneckova, Manuela; Krasensky, Jan; Kubala Havrdova, Eva; Horakova, Dana (Neurological sciences, 2022)
PURPOSE: To identify the clinical and paraclinical markers of employment status in multiple sclerosis (MS). METHODS: This was a cross-sectional sub-study investigating 1226 MS patients. To minimalized confounding effect, two groups of patients, matched by sex, age, and education, were selected: 307 patients with full time employment and 153 unemployed patients receiving disability pension. We explored associations between employment status and Expanded Disability Status Scale (EDSS), 25 Foot Walk Test (25FWT), Nine Hole Peg Test (9HPT), Brief International Cognitive Assessment for MS (BICAMS), Paced Auditory Serial Addition Test (PASAT), Beck Depression Inventory (BDI), SLOAN charts (SLOAN), and brain volumetric MRI measures. RESULTS: Both groups differed significantly on all variables of interest (p < 0.001). In the univariate analyses, EDSS, SDMT (Symbol Digit Modalities Test) adjusted for BDI, 25FWT, and 9HPT best explained variability in vocational status. In multivariate analyses, the combination of EDSS, 25FWT, SDMT, BDI, and corpus callosum fraction (CCF) explained the greatest variability. As a next step, after patients were matched by EDSS, differences in SDMT, 25FWT (both p < 0.001), 9HPT, CCF, and T2 lesion volume were still present (all p < 0.005) between both groups. The best multivariate model consisted of SDMT, BDI, and T2 lesion volume. CONCLUSIONS: EDSS, walking ability, cognitive performance, and MRI volumetric parameters are independently associated with employment status.
Keywords: Work disability; Magnetic Resonance Imaging; Disability Evaluation; magnetická rezonanční tomografie; Humans; neuropsychologické testy; MRI; Multiple Sclerosis; posuzování pracovní neschopnosti; Employment status; lidé; Employment; Gait impairment; Multiple sclerosis; Neuropsychological Tests; roztroušená skleróza; zaměstnanost; Cross-Sectional Studies; Cognitive impairment; průřezové studie